Socioeconomic differentials in child stunting in rural and urban areas in Zambia - Mushinge, Douglas (Health Economics Unit, 2020)
Child stunting remains one of the biggest public health concerns in Zambia and other low and middle-income countries (LMICs). A formidable challenge faced in improving child health outcomes in LMICs includes persistent socioeconomic and residential disparities. Despite achieving an overall decline in the prevalence of child stunting over the past decades, children residing in rural areas and less-privileged households continue to fall behind their peers from urban areas and wealthier households in Zambia and other LMICs. Notably, studies have shown that children residing in rural areas and less privileged households have a higher risk and burden of stunted growth in sub-Saharan Africa (SSA). However, basic rural-urban differentiation in child stunting can potentially conceal wealth differentials that exist within rural and urban areas. Specifically, cross country analyses have revealed that wealth differentials were higher in urban areas compared to rural areas; and higher than the overall urban-rural odds of stunting among children under five years of age. Using data from the 2013/14 Zambia Demographic Health Survey (ZDHS), differences in the relationship between socioeconomic status and child stunting in urban and rural areas of Zambia were assessed in this study. Furthermore, the study examines the effect of socioeconomic status and residence type in predicting child stunting prevalence in Zambia. To achieve these, the thesis used chi-square tests and logistic regression analysis. To the best of my knowledge, this is the first single-country analysis primarily focused on Zambia that has disaggregated the effect of predictors of child stunting by residence type. It is anticipated that the results of this dissertation will broaden the knowledge-base on wealth and residential differentials in child nutritional outcomes in Africa and thereby provide useful information to policymakers and technocrats in Zambia. Overall, the findings indicate that children under five years who reside in urban areas and poorer households have a higher likelihood of becoming stunted compared to their peers in rural and wealthier households. However, the relationship between child stunting and household wealth (SES) differs slightly after segregating by residence type. In both rural and urban areas, there is a consistent inverse relationship between the odds of stunted growth among under-fives and SES. Furthermore, these findings indicate that socioeconomic differentials are wider in rural areas compared to urban areas and much wider than the overall rural-urban odds ratios in Zambia. These findings could possibly be because of socioeconomic inequalities in child stunting that are higher in rural areas than urban areas. However, there is a need for further research to examine the causes of differentials in child stunting that may exist in rural and urban locations of Zambia.